2005
DOI: 10.17221/3621-pse
|View full text |Cite
|
Sign up to set email alerts
|

The use of molecular markers for characterisation of spring barley for breeding to Fusarium head blight resistance

Abstract: Fusarium head blight (FHB) is a barley disease, which occurs every year in various areas of barley cultivation all over the world and the increasing incidence has been confirmed in the Czech Republic also during the last years. We aimed to emply AFLP (Amplified fragment length polymorphism) and SSR (Single sequence repeats) markers to describe diversity among breeding lines with a sufficient level of resistance towards FHB and to find marker(s) associated with the analysed traits. The number of eight accession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The current study indicated that the joint analysis of AFLP and SSR is very effective for phylogenetic analysis of Citrullus spp. Studies such as Špunarová et al (2005) in barley, Gillaspie et al (2005) in Vigna , Maluf et al (2005) in Coffea , Saini et al 2004 in rice, Perumal et al (2007) in sorghum are few examples of copious published works, where joint analysis of AFLP and SSR datasets proved that these markers analyzed together have unprecedented utility for phylogenetic studies. Instead of generating a particular sequence-specific tree that does not necessarily reflect the true species tree, especially among the closely related and potentially interbreeding species such as Citrullus spp., where reticulate evolution might have occurred, the simultaneous analysis of many loci representing the whole genome has the potential to generate true phylogenies.…”
Section: Discussionmentioning
confidence: 99%
“…The current study indicated that the joint analysis of AFLP and SSR is very effective for phylogenetic analysis of Citrullus spp. Studies such as Špunarová et al (2005) in barley, Gillaspie et al (2005) in Vigna , Maluf et al (2005) in Coffea , Saini et al 2004 in rice, Perumal et al (2007) in sorghum are few examples of copious published works, where joint analysis of AFLP and SSR datasets proved that these markers analyzed together have unprecedented utility for phylogenetic studies. Instead of generating a particular sequence-specific tree that does not necessarily reflect the true species tree, especially among the closely related and potentially interbreeding species such as Citrullus spp., where reticulate evolution might have occurred, the simultaneous analysis of many loci representing the whole genome has the potential to generate true phylogenies.…”
Section: Discussionmentioning
confidence: 99%
“…Except for one genotype (01C0509112), all of the H. marinum accessions were moderately resistant to FHB in the greenhouse tests, probably reflecting their rather humid place of origin, where the pathogen spreads easily and where plants have to cope with pathogen attack, exemplifying their adaptation to environmental factors, as indicated previously [ 45 , 46 , 47 ]. SSR markers linked to disease resistance in barley did not amplify the same alleles on the studied loci that we found in the resistant barley cultivars Chevron and Frederikson [ 48 ]. The size variability of SSRT alleles was considerable.…”
Section: Discussionmentioning
confidence: 84%